Pod wierzchołkiem góry lodowej: zmieniająca się rola nauczyciela w świetle izraelskiej reformy oświaty pt. „Uczenie się z głową” - Fahoum, Ima (Studia Edukacyjne, 2019)
To cope with the challenges of the 21st century, a new Israeli educational reform, “Israel is moving up a grade” (known as Israel Ola Kita), was announced in 2014 by the former Minister of Education, Shai Piron, with the aim of assimilating the principles of meaningful learning in schools. A publication of the Ministry of Education, Something Good is Happening Now (2014) presented the policy and milestones for realizing the reform across the educational continuum.The current article highlights the complexities involved in the underlying reform principles concerning the change in the teacher’s role and argues the urgent need for considerations of these complexities through an expanded view of teachers’ professional development (TPD)with the aim of promoting deep-seated change rather than a superficial ‘signaling’ of the reform.